2019
DOI: 10.1111/1365-2656.12936
|View full text |Cite
|
Sign up to set email alerts
|

Energetic investment associated with vitellogenesis induces an oxidative cost of reproduction

Abstract: Oxidative stress is a potential cost of reproduction, but conclusive evidence for this relationship is lacking. The goal of this study was to serially assess across a seasonal gradient the relationship between reproduction, circulating plasma energy metabolites and oxidative state. Here, we examine a study animal ideally suited to test for the oxidative costs of reproduction: the Allen Cays Rock Iguana. Female rock iguanas reproduce at varying frequencies, often skipping years, allowing for a comparison betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 52 publications
4
27
0
Order By: Relevance
“…Our models predicted notable increases in H:L ratios with tick burden for larger iguana hosts, while these ratios remained stable in medium‐sized iguanas and decreased in smaller iguanas. All iguanas in this study were sexually mature and presumably subject to similar stressors associated with mating, reproduction, nest construction, and defense (Knapp & Owens, ; Webb, Iverson, Knapp, DeNardo, & French, ) supporting the supposition that higher H:L ratios with increasing tick burdens in larger iguanas are an immunological response associated with increased energy expenditures in certain hosts (Sheldon & Verhulst, ).…”
Section: Discussionsupporting
confidence: 60%
“…Our models predicted notable increases in H:L ratios with tick burden for larger iguana hosts, while these ratios remained stable in medium‐sized iguanas and decreased in smaller iguanas. All iguanas in this study were sexually mature and presumably subject to similar stressors associated with mating, reproduction, nest construction, and defense (Knapp & Owens, ; Webb, Iverson, Knapp, DeNardo, & French, ) supporting the supposition that higher H:L ratios with increasing tick burdens in larger iguanas are an immunological response associated with increased energy expenditures in certain hosts (Sheldon & Verhulst, ).…”
Section: Discussionsupporting
confidence: 60%
“…On the contrary, Webb et al (2018) found that increased reproductive investment (as measured by follicle number) was associated with increased ROMs in the lizard Cyclura cychlura inornata. Importantly, Webb et al (2018) measured this effect during vitellogenesis, thus pointing to this period as being key to understanding the relationship between reproductive investment and ROM production. A similar pattern of higher reactive oxygen metabolite production earlier in the reproductive cycle is also found in snakes (Antaresia childreni, Stahlschmidt et al, 2013) and birds (Sula leucogaster, Montoya et al, 2016).…”
Section: Maternal Physiology and Reproductionmentioning
confidence: 83%
“…This result suggests that both ROM production and reproductive investment could be correlated via some unmeasured physiological parameter representing overall 'individual quality': higher-quality individuals are able to both invest more in reproduction and meet energetic demands while producing fewer potentially detrimental by-products (Wilson and Nussey, 2010). On the contrary, Webb et al (2018) found that increased reproductive investment (as measured by follicle number) was associated with increased ROMs in the lizard Cyclura cychlura inornata. Importantly, Webb et al (2018) measured this effect during vitellogenesis, thus pointing to this period as being key to understanding the relationship between reproductive investment and ROM production.…”
Section: Maternal Physiology and Reproductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In squamate reptiles, this mode of provisioning to the developing embryo implies a temporal dissociation in resource allocation during reproduction. The major allocation of energy to reproduction in females occurs during vitellogenesis, which may involve higher oxidative damage and lower antioxidant defences (Webb, Iverson, Knapp, DeNardo, & French, ). Post‐ovulation and up to oviposition (oviparous species) or parturition (viviparous species), maternal reproductive effort is then oriented onto regulation of body temperature through behavioural means and water/oxygen supply, so that embryos can convert yolk into somatic tissues (Lourdais, Lorioux, Dupoué, Wright, & DeNardo, ; Vleck, ).…”
Section: Introductionmentioning
confidence: 99%